2022
DOI: 10.3389/fsurg.2022.810479
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Surgical Margin in Hepatectomy on Patients With Hepatocellular Carcinoma: A Meta-Analysis of Observational Studies

Abstract: ObjectiveThis study aims to comprehensively evaluate the prognostic impact of the surgical margin in hepatectomy on patients diagnosed with hepatocellular carcinoma (HCC).MethodsA comprehensive and systematic search for eligible articles published in English before July 2021 was conducted across PubMed, Cochrane Library, Web of Science, and Embase electronic databases. The overall survival (OS) and disease-free survival (DFS) were the primary endpoints.ResultsIn total, 37 observational studies with 12,295 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Due to the specific biological behaviors of HCC, such as its susceptibility to microvascular invasion, the status of the HCC resection margin is an established prognostic factor and most authors suggest a wide-margin ([ 7-10 mm) hepatectomy for HCC. [23][24][25] The Chinese Guidelines for the Diagnosis and Treatment of Primary Liver Cancer also suggest that the surgical margin for HCC should be greater than 10 mm away from the tumor boundary. 26 Recent studies have shown that the use of ICG fluorescent staining of hepatic lesions may help ensure negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the specific biological behaviors of HCC, such as its susceptibility to microvascular invasion, the status of the HCC resection margin is an established prognostic factor and most authors suggest a wide-margin ([ 7-10 mm) hepatectomy for HCC. [23][24][25] The Chinese Guidelines for the Diagnosis and Treatment of Primary Liver Cancer also suggest that the surgical margin for HCC should be greater than 10 mm away from the tumor boundary. 26 Recent studies have shown that the use of ICG fluorescent staining of hepatic lesions may help ensure negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgical margins, a recent meta‐analysis found that margin width was associated with prognosis in Eastern but not Western countries. [ 2 ] Notwithstanding the relevance of specific risk factors not included in the analysis, we recognize that the sample size of our study limits accommodation of an increasingly large number of variables in the models without compromising stability. In order to address this, we encourage well‐designed multicenter studies with clearly defined variables and endpoints.…”
mentioning
confidence: 99%